Terrestrial Plants Around Historical Kawasoti Lake, Nawalpur District, Nepal - Asmit Neupane; Sachin Timilsina; Pooja Dumre (CV. Literasi Indonesia, 2022)
Historical Kawasoti Lake is an excellent hub for floral and faunal diversity located in the Bhabhar region of the Southern Nawalpur district. This study was carried out to access the status and diversity of terrestrial floral species around the Lake area. A species-area curve method was employed to determine the sampling quadrants and the area was surveyed and sampled by foot trail for data collection. A total of 19 sample quadrants each of 10m*10m for tree species and a nested plot of 3*3m for shrubs and 1*1m for herbs were laid by foot trail within each quadrant. The collected data were analyzed and the Important Value Index (IVI)of only tree species was calculated in MS- Excel. A total of 66 terrestrial plant species of 38 different families were recorded, among which 25 were trees (38%), 27 herbs (41%), 12shrubs (18%), and 2 climber species (3%). Among 38 families, the Asteraceae family was dominant, followed by Poaceae, Lamiaceae, Moraceae, Malvaceae, Amaranthaceae, Apocynaceae, Fabaceae, and so on. Among 25 tree species, Moraceae was the most dominant family followed by Meliaceae, Rubiaceae, Malvaceae, and so on. Shorea robusta of the Dipterocarpaceae family has the highest IVI (62.16) followed by Dalbergia sissoo of the Fabaceae family (24.37), Ziziphus mauritiana of Malvaceae family (22.87), Melia azedarach of Meliaceae family (21.06), and least of Carica papaya of Caricaceae family (3.71). The result shows the floristic diversity and species richness around the lake area. So, further conservation programs need to be carried out in the future to conserve the ecological and social diversity of this lake sustainably. Also, this study will provide baseline information for plant specialists, foresters, and biologists to enhance the conservation of this floral species in this lake and also in different lake zones of Nepal.